Factors Associated With Postictal Agitation After Electroconvulsive Therapy. Issue 1 (5th November 2021) - Allen, Nicholas D.; Allison, Clayton L.; Golebiowski, Raphael; Janowski, John Patrick B.; LeMahieu, Allison M.; Geske, Jennifer R.; Rasmussen, Keith G.
Abstract : Objective: This study investigated the occurrence of postictal agitation (PA) in patients undergoing an acute series of electroconvulsive therapy (ECT) and further explored patient and treatment variables associated with PA. Methods: Charts were retrospectively searched for patients undergoing an acute series of ECT. Postictal agitation was identified by the administration of a sedative after ECT. Demographic, diagnostic, medication, and ECT variables that could also be associated with PA were collected and accounted for in statistical analysis. Results: In this population, 22 of 156 patients experienced PA. Associations that reached statistical significance included sex, weight, active substance use disorder, seizure duration (as observed by motor movements), and waking time. Only seizure duration and waking time maintained significance after multivariable analysis. Conclusions: These data identify clinical factors that could help predict PA. Patients with greater weight, male sex, or an active substance use disorder ought to be carefully monitored for PA, and staff in the recovery suite should be especially vigilant about such patients with longer seizures and waking times.